Novel near-infrared carboxylated 1, 3-indandione sensitizers for highly efficient flexible dye-sensitized solar cells1. Issue 64 (18th August 2015) - Shibayama, Naoyuki; Inoue, Yukiko; Abe, Masahiro; Kajiyama, Shingo; Ozawa, Hironobu; Miura, Hidetoshi; Arakawa, Hironori
<x xml:space="preserve">Abstract</x> The novel near-infrared organic dyes were designed for use in plastic-substrate dye sensitized solar cells. As a result, η of 5.76% was achieved.